Do Gıg Workers Enjoy Work-Lıfe Balance? Explorıng The Influencıng Factors For Work-Lıfe Balance Among The Gıg Workers - Tan Yi; Low Mei Peng (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
The growing trend of the gig economy (GE) globally and nationally has contributed to the rise of gig workforce to reducing unemployment. Also, the increased demand for gig services in Malaysia has made GE as a recognised new economic driver. This is observed with the introduction of i-Saraan and e-rezeki. GE has opened up many employments opportunities with the option of maintaining work-life balance (WLB). This flexibility aligns with the desire of many Malaysians and millennials. With that said, what are the main influencing factors that contributed to the gig workers’ WLB remain unexplored. This study aims to determine whether job autonomy (JA), work engagement (WE), and mental health (MH) are positively related to WLB via spillover theory. A total of 212 self-administered surveys were collected from the Malaysian low-skilled gig workers through judgmental and snowball sampling. Variance-Based structural equation modeling (VB-SEM) approach was to validate proposed hypotheses. The findings revealed that JA, WE, and MH had significant positive effects on WLB. Besides filling the research gap, this study provides some insights on the gig economy's sustainability, improves overall gig workers’ well-being in attaining WLB.